"IMPROVING THE TEACHING OF THE SUBJECT" EDUCATION" BASED ON MULTIMEDIA TECHNOLOGIES " (ON THE EXAMPLE OF PRIMARY CLASSES) (American Journal of Interdisciplinary Research and Development, 2022)
Today, when teaching the subject “upbringing” for Primary School students, teaching with the help of today's modern multimedia technologies and their involvement in the lesson through various skills is a priority. Changes in the system of primary education are developing in a wide range, and the consciousness of young people is implementing the knowledge learned through various gadgets.